2008
DOI: 10.1111/j.1365-2966.2008.13783.x
|View full text |Cite
|
Sign up to set email alerts
|

The mass density field in simulated non-Gaussian scenarios

Abstract: n this work, we study the properties of the mass density field in the non-Gaussian world models simulated by Grossi et al. In particular, we focus on the one-point density probability distribution function of the mass density field in non-Gaussian models with quadratic non-linearities quantified by the usual parameter fNL. We find that the imprints of primordial non-Gaussianity are well preserved in the negative tail of the probability function during the evolution of the density perturbation. The effect is al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 47 publications
14
68
0
Order By: Relevance
“…This condition guarantees that the statistical properties of the cosmological density field are modeled accurately throughout the range of scales spanned by the simulation. In particular, this is fundamental for probing the imprints of primordial non-Gaussianities on large-scale structure, a topic of current interest (e.g., Dalal et al 2008;Grossi et al 2008;Hikage et al 2008). These results have two implications.…”
Section: Discussionmentioning
confidence: 99%
“…This condition guarantees that the statistical properties of the cosmological density field are modeled accurately throughout the range of scales spanned by the simulation. In particular, this is fundamental for probing the imprints of primordial non-Gaussianities on large-scale structure, a topic of current interest (e.g., Dalal et al 2008;Grossi et al 2008;Hikage et al 2008). These results have two implications.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratic coupling f NL 2 also affect the matter power spectrum at leading order [38,84], positive values of f NL increasing the small scale power. However, the relative size of this k-dependent correction, m ðk; f NL Þ, is at a per cent level only in the weakly nonlinear regime k & 0:1h Mpc À1 [53,85] and fades rapidly as one goes to larger scales.…”
Section: B Biasmentioning
confidence: 99%
“…Another recent result has shown that the nonlinear dark matter power spectrum alone is sensitive to the presence of f NL [16,17,19,21,30]. This prompted [31] to propose that the statistics of the initial conditions could be tested through weak gravitational lensing by large-scale structure, in particular through measurement of the twopoint shear correlation functions.…”
Section: Introductionmentioning
confidence: 99%